Development and Validation of Performance Appraisal Scale (PAS-SSTs) for Secondary School Teachers (Journal of Asian Development Studies, 2013)
The major purpose of this study is to develop a research tool for evaluating the performance of secondary school teachers. The data were collected from 200 teachers working at public and private secondary schools (100 from each sector) of Faisalabad Division. Items were derived from already conducted related studies. The experts’ opinion was also taken in this regard. Main factors involved in Performance Appraisal Scale for Secondary School Teachers (PAS-SSTs) were classroom management, subject knowledge, teaching and learning environment, planning and presentation, professional conduct and management of work schedule. Performance appraisal scale contained 29 items. These items were organized and piloted upon 200 teachers from both public and private sector schools. The reliability coefficient (Cronbach alpha) value was measured which was 0.926. A Confirmatory Factor Analysis (CFA) was used to validate the PAS-SSTs tool. Fit indices for Performance Appraisal Scale showed an acceptable model fit. Each item was well above the threshold value 0.35 in factor loadings.